Vacuum brazing and heat treatment process for GH2909 alloy part
Through vacuum brazing heat treatment and primary aging treatment, the problem of poor strength and stability of GH2909 alloy components at high temperatures is solved, the coordinated improvement of strength and plasticity is achieved, and the process flow is simplified and the cost is reduced.
Patent Information
- Application Number
- CN202411927667.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-25
AI Technical Summary
GH2909 alloy components have poor strength and stability at high temperatures. The existing heat treatment process is complex and costly. It is difficult to improve the strength and plasticity synergistically, and the strong plasticity change law is difficult to accurately predict.
The vacuum brazing heat treatment process is used to combine the primary aging treatment. By regulating the temperature increase rate and cooling rate, uniform precipitation of the γ′ phase in the alloy and further aging treatment are promoted, the process flow is simplified and the cost is reduced.
The room temperature and high temperature tensile strength and yield strength of GH2909 alloy components have been significantly improved, and the stability and plasticity of the material have been improved. The standard deviation value is reduced by more than 30%, solving the problems of strength failure and stability.
Smart Images

Figure CN119897541A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat treatment of high-temperature alloys, in particular to a vacuum brazing and heat treatment process for GH2909 alloy parts. Background Art
[0002] High-temperature alloy refers to a type of metal material based on iron, nickel and cobalt, which can work for a long time at high temperatures above 600°C and under certain stresses. It has excellent high-temperature strength, good oxidation resistance and thermal corrosion resistance, good fatigue performance, fracture toughness and other comprehensive properties. It is also called "superalloy" and is mainly used in the aerospace and energy fields.
[0003] Among them, GH2909 is a high-strength nickel-based alloy, mainly used for engineering applications in high temperature and corrosive environments. It usually has good oxidation resistance and corrosion resistance, and is suitable for key components in aerospace, petrochemical and other fields. The chemical composition of GH2909 contains elements such as nickel, chromium, iron, and molybdenum, which enable it to maintain excellent mechanical properties and stability under high temperature conditions. The application range of this alloy includes gas turbine engine components, heat exchangers, and other equipment that requires high temperature resistance and corrosion resistance. GH2909 has relatively good processing performance and can be formed and welded by various methods.
[0004] After the standard short-aging heat treatment of GH2909 alloy used in welding rings, the size of the γ′ phase in the alloy matrix is large, the density is not high, and after two-step aging, the process flow is complicated. The tensile strength and yield strength of the parts sometimes do not meet the standards or the margin of the standards is very small and unstable.
[0005] However, "The Influence of Forging Process and Heat Treatment System on the Structure and Properties of GH2909 Alloy" (Wang Xincai, Special Steel Technology, P8-9, P14, Vol.19(75), 2013.No.2) discloses the influence of forging process and heat treatment preparation on the structure, and shows that the precipitates after the secondary solid solution + two-stage aging heat treatment are significantly more than the precipitates after the primary solid solution + two-stage aging heat treatment; although the strength and hardness can be improved, the forging process needs to be limited, the temperature of the solid solution heat treatment is not high, and the effect of the solid solution treatment needs to be further improved; the elongation of the obtained material is low.
[0006] "Research on the Performance of Heat Treatment Process of GH2909" (Fan Qianwei, Sun Yan; Metal Processing: Hot Processing, Issue 13, 2015, pp. 18-21, 4 pages in total) discloses that as the solution temperature increases, the strength increases and the plasticity and toughness decrease; as the aging temperature increases, the strength decreases and the plasticity and toughness increases. Increasing the silicon content in the raw materials is beneficial to increasing the amount of ε phase and ε″ phase in the alloy, thereby improving the high-temperature notch sensitivity of the alloy; it can be seen that its heat treatment process is mainly solution treatment and aging treatment, and the proportion of the two processes is adjusted according to the required strength and plasticity and toughness. From the above literature, it can be seen that at least one solution treatment + two-stage aging heat treatment is required. Summary of the invention
[0007] In order to solve the technical problems in the prior art such as poor strength and stability of GH2909 alloy parts at room temperature and high temperature, high cost of one solution treatment + two aging treatment processes, low efficiency of two solution treatments + two aging treatment processes, poor synergistic improvement of strength and plasticity, and difficulty in accurately predicting the law of strength and plasticity changes, the present invention proposes a vacuum brazing and heat treatment process for GH2909 alloy parts that can solve the above problems. The technical solution is as follows:
[0008] A vacuum brazing and heat treatment process for GH2909 alloy parts, the vacuum brazing and heat treatment process for GH2909 alloy parts comprises the following steps:
[0009] S1. Surface pretreatment: pretreating the surface of the GH2909 alloy component to obtain a GH2909 alloy component with a clean surface;
[0010] S2, vacuuming: Place the GH2909 alloy parts with cleaned surfaces in S1 in a vacuum brazing furnace and vacuumize;
[0011] S3, vacuum brazing heat treatment: the vacuum brazing furnace is heated up, and the GH2909 alloy parts with cleaned surfaces in S1 are subjected to vacuum brazing heat treatment, and then cooled with the furnace, and then air-cooled after furnace cooling, to obtain the GH2909 alloy parts after vacuum brazing heat treatment;
[0012] S4. Primary aging treatment: Perform primary aging treatment on the GH2909 alloy parts after S2 vacuum brazing heat treatment, and obtain GH2909 alloy parts with improved room temperature strength and stability after air cooling.
[0013] Optionally, the GH2909 alloy component in S1 is in the shape of a bar with a size of Φ150 mm, Φ200 mm or Φ220 mm, and is treated with a standard double aging heat treatment 2 (845°C×(4±0.5)h / FC→620°C×(4±0.5)h / AC); the room temperature tensile strength is 1190-1250MPa, with a standard deviation of 18-29MPa; the room temperature yield strength is 930-960MPa, with a standard deviation of 9-17MPa; the room temperature elongation is 13.7-17.8%, with a standard deviation of 0.9-1.5%; the room temperature The cross-sectional shrinkage rate is 22-33%, and the standard deviation is 3.9-5.8%; the room temperature hardness is 350-365HB, and the standard deviation is 5-11HB; the tensile strength at 650℃ is 860-970MPa, and the standard deviation is 19-31MPa; the yield strength at 650℃ is 715-800MPa, and the standard deviation is 25-43MPa; the elongation at 650℃ is 12.5-20.4%, and the standard deviation is 2.3-6.7%; the cross-sectional shrinkage rate at 650℃ is 26.0-40.5%, and the standard deviation is 4.5-8.9%.
[0014] Optionally, the shape of the GH2909 alloy component in S1 is annular, with dimensions of 400-600 mm in outer diameter, 300-500 mm in inner diameter, 70-90 mm in height, chord sampling, and the treatment state is standard double aging heat treatment 2 (845°C×(4±0.5)h / FC→620°C×(4±0.5)h / AC); the tensile strength at room temperature is 1200-1240 MPa, with a standard deviation of 15-27 MPa; the yield strength at room temperature is 910-970 MPa, with a standard deviation of 20-45 MPa; the elongation at room temperature is 14.0-18.8%, with a standard deviation of 1.2 -2.3%; the section shrinkage at room temperature is 24-37%, with a standard deviation of 3.6-5.9%; the room temperature hardness is 350-365HB, with a standard deviation of 6-11HB; the tensile strength at 650℃ is 930-970MPa, with a standard deviation of 20-31MPa; the yield strength at 650℃ is 770-810MPa, with a standard deviation of 25-43MPa; the elongation at 650℃ is 12.5-29.4%, with a standard deviation of 3.8-9.7%; the section shrinkage at 650℃ is 26.0-44.5%, with a standard deviation of 6.7-10.9%.
[0015] Optionally, the shape of the GH2909 alloy component in S1 is a square billet with a size of 90mm×90mm×90mm, and the treatment state is standard double aging heat treatment 2 (845℃×(4±0.5)h / FC→620℃×(4±0.5)h / AC); the tensile strength at room temperature is 1200-1230MPa, and the standard deviation is 15-28MPa; the yield strength at room temperature is 890-945MPa, and the standard deviation is 19-35MPa; the elongation at room temperature is 14.7-18.2%, and the standard deviation is 0.7-2.1%; the cross section at room temperature is The shrinkage rate is 26-37%, and the standard deviation is 2.7-5.9%; the room temperature hardness is 360-365HB, and the standard deviation is 2-7HB; the tensile strength at 650℃ is 935-980MPa, and the standard deviation is 15-25MPa; the yield strength at 650℃ is 784-820MPa, and the standard deviation is 20-40MPa; the elongation at 650℃ is 15.5-29.4%, and the standard deviation is 3.8-9.3%; the cross-sectional shrinkage rate at 650℃ is 27.0-47.5%, and the standard deviation is 6.7-11.9%.
[0016] Optionally, the pretreatment in S1 includes removing the surface oxide layer or oil stains, and finally cleaning and drying to obtain a GH2909 alloy component with a clean surface; the vacuuming in S2 is to vacuumize to a pressure not greater than 10 -3 Pa.
[0017] Optionally, the temperature of the vacuum brazing heat treatment in S3 is 1000-1040°C, and the temperature is kept for 10-30min; it needs to be heated to 550-650°C at a rate of 10-15°C / min and kept for 10-20min, then heated to 880-940°C at a rate of 15-20°C / min and kept for 15-30min, and finally heated to a brazing insulation temperature of 1000-1040°C at a rate of 5-10°C / min; then cooled with the furnace at a cooling rate of 3-8°C / min, cooled with the furnace to below 80°C and directly taken out of the furnace, and the air cooling rate is 50-80°C / min, and the insulation time after reaching the brazing temperature of 1000-1040°C in this stage is 10-30min.
[0018] Optionally, the temperature of the primary aging treatment in S4 is 620±10°C, kept at this temperature for 8±0.5h, and the heating rate is 10-30°C / min; taken out and air-cooled to room temperature, and the air-cooling rate is 50-80°C / min.
[0019] Optionally, the shape of S3 is a rod with a size of Φ150mm, Φ200mm or Φ220mm, and the treatment state is vacuum brazing + primary aging ((1000-1040)℃×(15-30)min / FC+620℃×(8±0.5)h / AC); the tensile strength at room temperature is 1350-1380MPa, with a standard deviation of 10-17MPa; the yield strength at room temperature is 1020-1050MPa, with a standard deviation of 9-14MPa; the elongation at room temperature is 17.9-23.2%, with a standard deviation of 0.8-1.7%; The cross-sectional shrinkage rate is 27-39%, and the standard deviation is 2.9-4.8%; the room temperature hardness is 370-385HB, and the standard deviation is 3-8HB; the tensile strength at 650℃ is 1005-1025MPa, and the standard deviation is 12-26MPa; the yield strength at 650℃ is 820-870MPa, and the standard deviation is 25-33MPa; the elongation at 650℃ is 11.5-21.4%, and the standard deviation is 2.3-5.7%; the cross-sectional shrinkage rate at 650℃ is 35.0-40.5%, and the standard deviation is 2.7-4.9%.
[0020] Optionally, the shape of S3 is annular, the size is 400-600mm in outer diameter, 300-500mm in inner diameter, 70-90mm in height, chord sampling, and the treatment state is vacuum brazing + primary aging ((1000-1040)℃×(15-30)min / FC+620℃×(8±0.5)h / AC); the tensile strength at room temperature is 1340-1370MPa, and the standard deviation is 11-15MPa; the yield strength at room temperature is 1025-1060MPa, and the standard deviation is 10-14MPa; the elongation at room temperature is 18.8-24.5%, and the standard deviation is 0. 7-1.4%; the section shrinkage at room temperature is 30-39%, with a standard deviation of 2.7-4.2%; the room temperature hardness is 370-385HB, with a standard deviation of 3-9HB; the tensile strength at 650℃ is 1000-1020MPa, with a standard deviation of 12-20MPa; the yield strength at 650℃ is 830-870MPa, with a standard deviation of 20-30MPa; the elongation at 650℃ is 11.5-20.4%, with a standard deviation of 3.7-5.1%; the section shrinkage at 650℃ is 35.0-41.5%, with a standard deviation of 2.7-3.8%.
[0021] Optionally, the shape of S3 is a square billet with a size of 90mm×90mm×90mm, and the treatment state is a standard double aging heat treatment 2 (845℃×(4±0.5)h / FC→620℃×(4±0.5)h / AC); the tensile strength at room temperature is 1200-1230MPa, and the standard deviation is 15-28MPa; the yield strength at room temperature is 890-945MPa, and the standard deviation is 19-35MPa; the elongation at room temperature is 14.7-18.2%, and the standard deviation is 0.7-2.1%; the cross-sectional shrinkage at room temperature is 26 -37%, standard deviation is 2.7-5.9%; room temperature hardness is 360-365HB, standard deviation is 2-7HB; tensile strength at 650℃ is 935-980MPa, standard deviation is 15-25MPa; yield strength at 650℃ is 784-820MPa, standard deviation is 20-40MPa; elongation at 650℃ is 15.5-29.4%, standard deviation is 3.8-9.3%; cross-sectional shrinkage at 650℃ is 27.0-47.5%, standard deviation is 6.7-11.9%.
[0022] Optionally, the final structure of the GH2909 alloy component after vacuum brazing + one-time aging consists of a γ solid solution with a volume fraction of 79.70-80.44%, a γ′ phase with a volume fraction of 12.97-13.43%, a Laves phase with a volume fraction of 4.06-5.36%, and an ε phase with a volume fraction of 1.86-2.06% (the γ solid solution is generally not studied, and the shape and size are not fixed); wherein, the γ′ phase is in the shape of a small sphere or a cube, with an average size of 18.46nm; the Laves phase is in the shape of a sphere or a short rod, with an average major axis length of 1.45-1.84μm and an average minor axis length of 0.75-0.86μm; the ε phase is in the shape of a needle, with an average length of 0.89-1.61μm.
[0023] Technical principle of the present invention:
[0024] During the vacuum brazing heat treatment and aging treatment process of the present invention:
[0025] First, in the vacuum brazing stage, in order to protect the heating components in the vacuum brazing furnace and ensure normal service life, a lower heating power and segmented heating method are adopted: 1. Heat to 550-650℃ at a rate of 10-15℃ / min and keep warm for 10-20min. The precipitation temperature of the alloy strengthening phase γ′ phase is about 560-720℃, and the precipitation temperature of the ε phase is 680-800℃, which is a softening phase. Therefore, during the first stage of insulation, a part of the γ′ phase is precipitated in the alloy but the ε phase is not precipitated to ensure that the strength and hardness of the alloy parts meet the support requirements during the entire brazing process; 2. Continue to heat to 880-940℃ at a rate of 15-20℃ / min and keep warm for 15-30min. The main purpose is to make the temperature in the furnace more uniform before the brazing process begins to avoid uneven temperature during the brazing process. In this process, a part of the Laves phase is precipitated at the grain boundary of the alloy, which plays a role in pinning the grain boundary and strengthening. Grain boundary effect ensures the plasticity of the alloy parts during brazing; 3. Heating to 1000-1040℃ (brazing temperature) at a rate of 5-10℃ / min and keeping warm for 10-30min for brazing. The standard solution temperature of GH2909 alloy in the alloy manual is 980℃, and the complete dissolution temperature of Laves phase is 1050℃. Therefore, the brazing process is equivalent to a solid solution heat treatment, but some Laves are not dissolved and are intermittently distributed at the grain boundaries in smaller sizes; furnace cooling is adopted in the cooling rate stage, and the cooling rate is 3-8℃ / min. The vacuum brazing furnace has vacuum characteristics, and it is not easy to directly take out the sample for cooling. Therefore, the conventional method previously selected the Ar gas cooling method (cooling rate of about 100℃ / min), but according to the alloy CCT curve results, the cooling rate cannot make the γ′ phase precipitate. The present invention adopts furnace cooling to actively reduce the cooling rate, so that the fine γ′ phase is first dispersed and precipitated in the alloy.
[0026] Then comes the aging stage. In order to protect the heating furnace and reduce energy consumption, a simple and low-temperature primary aging is adopted: the temperature is raised to 620±10℃ at a rate of 10-30℃min and kept for 8±0.5h, then taken out and air-cooled. The conventional method before brazing is standard short-time double aging (745℃×(4±0.5)h / FC→620℃×(4±0.5)h / AC). While the process is complicated, a larger cubic γ′ phase is obtained, which contributes generally to the strength. The primary aging of the present invention is at a lower temperature, which will not cause the γ′ phase precipitated in the cooling stage after welding to grow excessively, and is accompanied by additional supplementary precipitation, which is higher than the commonly used heat treatment in terms of strength improvement, and the total plasticity can be kept good.
[0027] In summary, the selection of heating rate is mainly to protect the normal use of vacuum brazing furnace and heating furnace. When the heating power is sufficient, the temperature in the furnace should be kept as uniform as possible. As for the selection of cooling rate, only furnace cooling with reduced cooling rate after brazing has an effect on the microstructure of the alloy, which has been explained in detail above. The selection of air cooling for subsequent aging is based on national standards and has little effect on the alloy structure.
[0028] Compared with the prior art, the above technical solution has at least the following beneficial effects:
[0029] The above scheme proposes a vacuum brazing and heat treatment process for GH2909 alloy parts, which can solve the technical problems in the prior art that the room temperature and high temperature strength and stability of GH2909 alloy parts are poor, the cost of one solution treatment + two aging treatment processes is high, the efficiency of two solution treatments + two aging treatment processes is low, the strength and plasticity cannot be well improved in coordination, and the change law of strength and plasticity is difficult to accurately predict.
[0030] The present invention replaces processes such as one solution treatment and two aging treatments, two solution treatments and two aging treatments by vacuum brazing heat treatment and one aging treatment, thereby shortening the process flow, reducing the process cost and improving the process efficiency.
[0031] The present invention regulates the heating rate and cooling rate during vacuum brazing heat treatment and aging treatment, so that the alloy γ′ phase is precipitated in a large and uniform manner during the cooling stage after vacuum brazing heat treatment, and further precipitates during the one-step aging heat treatment, and no excessive growth of the structure and phase transformation occur during these processes. After the heat treatment, the uniformity of the γ′ phase distribution inside the grains is improved, which has an unexpected effect in improving the strength and stability of the alloy parts.
[0032] The results of multiple sets of mechanical property tests of the present invention show that compared with traditional brazing and aging processes, after treatment by the method of the present invention, the room temperature tensile strength and yield strength of the alloy are increased by 120 and 90 MPa respectively, and the standard deviation of the room temperature yield strength is reduced by more than 30%.
[0033] In summary, compared with other traditional methods, the method of the present invention performs short-time and high-efficiency heat treatment on GH2909 alloy parts through vacuum brazing heat treatment and one-time aging treatment, so that the room temperature strength and stability, high temperature strength and stability of the alloy parts are synergistically improved; the method is simple and easy to operate, green and environmentally friendly, low in cost, short in process, high in efficiency, and is conducive to large-scale industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 This is a distribution diagram of the γ′ phase in the alloy obtained by the vacuum brazing and heat treatment process of a GH2909 alloy component in Example 1 of the present invention.
[0036] Figure 2 This is a distribution diagram of the γ′ phase in the alloy obtained after vacuum brazing heat treatment + double aging process in comparative example 1 of the present invention. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is described below in conjunction with the accompanying drawings.
[0038] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.
[0039] In the embodiments of the present invention, "image" and "picture" may sometimes be used interchangeably. It should be noted that when the distinction between them is not emphasized, the meanings they intend to express are consistent.
[0040] In the embodiments of the present invention, sometimes a subscript such as W1 may be written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are the same.
[0041] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0042] Example 1
[0043] A vacuum brazing and heat treatment process for GH2909 alloy parts, wherein the elements are as follows by mass percentage: C 0.01%, Si 0.40%, Co 13.48%, Ni 38.06%, Ti 1.64, Nb 4.88%, Al 0.031%, Mo 0.04%, and the balance is Fe and unavoidable impurities; the vacuum brazing and heat treatment process for GH2909 alloy parts comprises the following steps:
[0044] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the GH2909 alloy component is in the shape of a rod, with a size of Φ150mm, a sampling size of Φ8mm, and a state before brazing of standard short-time double aging 2. The mechanical properties are shown in Table 1 below:
[0045] Table 1
[0046] Test temperature / ℃ Tensile strength / MPa Standard deviation / MPa Room temperature 1211、1192、1242、1228、1250、1219 19.3 650 900、865、885、935、895、921 22.8 Test temperature / ℃ Yield strength / MPa Standard deviation / MPa Room temperature 960、931、953、942、935、945 9.9 650 750、725、734、804、779、781 28.0 Test temperature / ℃ Elongation / % Standard Deviation / % Room temperature 13.5、15.4、17.1、14.4、15.4、14.1 1.2 650 11.5、12.7、17.5、21.2、24、16 4.4 Test temperature / ℃ Shrinkage after breaking / % Standard Deviation / % Room temperature 26、33、37、28、31、22 4.8 650 24、37、31、38、38、27 5.5 Test temperature / ℃ Hardness / HB Standard deviation / HB Room temperature 361.1、373.3、368.5、359.1、360.1、367.5 5.2 ;
[0047] S2. Vacuuming: Place the GH2909 alloy parts with cleaned surface in S1 into a vacuum brazing furnace and evacuate until the pressure is no more than 10 -3 Pa;
[0048] S3, vacuum brazing heat treatment: the vacuum brazing furnace is heated up, and the GH2909 alloy parts with cleaned surfaces in S1 are subjected to vacuum brazing heat treatment, the temperature of vacuum brazing heat treatment is 1000°C, and the temperature is kept for 30 minutes; the temperature is raised to 550°C at a rate of 10°C / min and kept for 10 minutes, and then the temperature is raised to 940°C at a rate of 15°C / min and kept for 10 minutes, and finally the temperature is raised to 1000°C at a rate of 5°C / min; after brazing is completed, the parts are cooled with the furnace at a cooling rate of 3°C / min, cooled to 80°C, taken out and air-cooled to room temperature at a cooling rate of 70°C / min, and the GH2909 alloy parts after vacuum brazing are obtained;
[0049] S4. Primary aging treatment: The GH2909 alloy parts after S3 vacuum brazing heat treatment were subjected to primary aging treatment at a temperature of 620°C for 8 hours at a heating rate of 20°C / min. After aging, the parts were taken out and air-cooled to room temperature at a rate of 70°C / min. GH2909 alloy parts were obtained after air cooling.
[0050] The GH2909 alloy component of this embodiment is in the shape of a rod, with a size of Φ150 mm and a sampling size of Φ8 mm. After vacuum brazing and primary aging, the mechanical properties are shown in Table 2 below:
[0051] Table 2
[0052] Test temperature / ℃ Tensile strength / MPa Standard deviation / MPa Room temperature 1381、1385、1377、1368、1370、1375 5.9 650 1010、999、1020、1012、1015、1016 4.9 Test temperature / ℃ Yield strength / MPa Standard deviation / MPa Room temperature 1024、1031、1025、1019、1034、1029 6.6 650 831、824、829、815、826、815 6.3 Test temperature / ℃ Elongation / % Standard Deviation / % Room temperature 19.1、19.1、20.4、21.5、18.9、20.1 0.9 650 12.4、11.6、13.8、23.0、17.5、15.5 3.8 Test temperature / ℃ Shrinkage after breaking / % Standard Deviation / % Room temperature 35、34、30、33、37、36 2.3 650 36、38、41、37、38、39 1.6 Test temperature / ℃ Hardness / HB Standard deviation / HB Room temperature 381.3、373.3、377.8、379.1、382.4、378.8 2.9 ;
[0053] like Figure 1As shown, the microstructure of the GH2909 alloy component prepared in this embodiment after vacuum brazing + one-time aging consists of 80.66% volume fraction of γ solid solution, 13.05% volume fraction of γ′ phase, 4.32% volume fraction of Laves phase and 1.97% ε phase (γ solid solution is generally not studied, and the shape and size are not fixed); among them, the shape of γ′ phase is fine spherical or cubic, with an average size of 18.41nm; the shape of Laves phase is spherical or short rod, with an average major axis length of 1.46μm and an average minor axis length of 0.77μm; the shape of ε phase is needle-shaped, with an average length of 1.53μm.
[0054] Comparative Example 1
[0055] A vacuum brazing and heat treatment process for GH2909 alloy parts, wherein the elements are as follows by mass percentage: C 0.01%, Si 0.40%, Co 13.48%, Ni 38.06%, Ti 1.64, Nb 4.88%, Al 0.031%, Mo 0.04%, and the balance is Fe and unavoidable impurities; the vacuum brazing and heat treatment process for GH2909 alloy parts comprises the following steps:
[0056] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the GH2909 alloy component is in the shape of a rod, with a size of Φ150 mm, a sampling size of Φ8 mm, and a state before brazing of standard short-time double aging 2. The mechanical properties are shown in Table 3 below:
[0057] Table 3
[0058]
[0059]
[0060] S2. Vacuuming: Place the GH2909 alloy parts with cleaned surface in S1 into a vacuum brazing furnace and evacuate until the pressure is no more than 10 -3 Pa;
[0061] S3, vacuum brazing heat treatment: the vacuum brazing furnace is heated up, and the GH2909 alloy parts with cleaned surfaces in S1 are subjected to vacuum brazing heat treatment, the temperature of vacuum brazing heat treatment is 1000°C, and the temperature is kept for 30 minutes; the temperature is raised to 550°C at a rate of 10°C / min and kept for 10 minutes, and then the temperature is raised to 940°C at a rate of 15°C / min, and kept for 10 minutes, and finally the temperature is raised to 1000°C at a rate of 5°C / min; after the brazing is completed, Ar gas is introduced for rapid cooling at a rate of 100°C / min, and after cooling to below 80°C, the parts are taken out and air-cooled to room temperature at a rate of 70°C / min, and the GH2909 alloy parts after vacuum brazing treatment are obtained;
[0062] S4. Two aging treatments: The GH2909 alloy parts after S3 vacuum brazing heat treatment were subjected to two aging treatments. The temperature was raised to 745°C at a rate of 20°C / min and kept at this temperature for 4 hours. Then, the parts were cooled to 620°C at a rate of 55°C / h and kept at this temperature for 4 hours. Then, the parts were taken out and air-cooled to room temperature at a rate of 50-80°C / min to obtain GH2909 alloy parts.
[0063] The shape of the GH2909 alloy component of this comparative example is a bar with a size of Φ150mm and a sampling size of Φ8mm; the tensile strength at room temperature is 1210-1250MPa, with a standard deviation of 15-27MPa; the yield strength at room temperature is 920-955MPa, with a standard deviation of 7-15MPa; the elongation at room temperature is 14.7-19.8%, with a standard deviation of 0.7-1.2%; the cross-sectional shrinkage at room temperature is 24-37%, with a standard deviation of 2.9-5.6%; The temperature hardness is 357-365HB, and the standard deviation is 5-8HB; the tensile strength at 650℃ is 880-950MPa, and the standard deviation is 17-33MPa; the yield strength at 650℃ is 745-800MPa, and the standard deviation is 26-40MPa; the elongation at 650℃ is 14.5-21.8%, and the standard deviation is 2.4-7.7%; the cross-sectional shrinkage at 650℃ is 27.0-42.5%, and the standard deviation is 4.7-9.2%.
[0064] like Figure 2 As shown, the microstructure of the GH2909 alloy component of this comparative example after vacuum brazing + one-time aging consists of 72.25% volume fraction of γ solid solution, 20.41% volume fraction of γ′ phase, 4.67% volume fraction of Laves phase and 2.67% ε phase (γ solid solution is generally not studied, and the shape and size are not fixed); among them, the shape of γ′ phase is cubic, and the average size is 29.38nm; the shape of Laves phase is spherical or short rod, with an average major axis length of 1.56μm and an average minor axis length of 0.79μm; the shape of ε phase is needle-shaped, with an average length of 1.74μm.
[0065] and Figure 1 Compared with the distribution of γ′ phase in the alloy after heat treatment in the embodiment shown in the figure, Figure 2 After the process treatment of Comparative Example 1, the distribution density of the γ′ phase in the alloy is lower and the size is larger.
[0066] From the comparison of the strength values of Comparative Example 1 and Example 1, it can be seen that the strength of the alloy obtained by treating the GH2909 alloy parts by the process described in the present invention is significantly improved compared with the strength after the traditional standard aging treatment, wherein the tensile strength is increased by an average of about 100MPa, and the yield strength is increased by an average of about 90MPa. In addition, the mechanical property stability of the GH2909 alloy is significantly improved after the heat treatment process of the present invention. The standard deviation of the yield strength at room temperature is reduced by more than 40%. The technical problem that the strength of the GH2909 alloy parts does not meet the standards or the surplus of the standards is small in the actual production process is solved.
[0067] Comparative Example 2
[0068] A vacuum brazing and heat treatment process for GH2909 alloy parts, wherein the elements are as follows by mass percentage: C 0.01%, Si 0.40%, Co 13.48%, Ni 38.06%, Ti 1.64, Nb 4.88%, Al 0.031%, Mo 0.04%, and the balance is Fe and unavoidable impurities; the vacuum brazing and heat treatment process for GH2909 alloy parts comprises the following steps:
[0069] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the GH2909 alloy component is in the shape of a rod, with a size of Φ150 mm, a sampling size of Φ8 mm, and a state before brazing of standard short-time double aging 2. The mechanical properties are shown in Table 4 below:
[0070] Table 4
[0071] Test temperature / ℃ Tensile strength / MPa Standard deviation / MPa Room temperature 1211、1192、1242、1228、1250、1219 19.3 650 900、865、885、935、895、921 22.8 Test temperature / ℃ Yield strength / MPa Standard deviation / MPa Room temperature 960、931、953、942、935、945 9.9 650 750、725、734、804、779、781 28.0 Test temperature / ℃ Elongation / % Standard Deviation / % Room temperature 13.5、15.4、17.1、14.4、15.4、14.1 1.2 650 11.5、12.7、17.5、21.2、24、16 4.4 Test temperature / ℃ Shrinkage after breaking / % Standard Deviation / % Room temperature 26、33、37、28、31、22 4.8 650 24、37、31、38、38、27 5.5 Test temperature / ℃ Hardness / HB Standard deviation / HB Room temperature 361.1、373.3、368.5、359.1、360.1、367.5 5.2 ;
[0072] S2. Vacuuming: Place the GH2909 alloy parts with cleaned surface in S1 into a vacuum brazing furnace and evacuate until the pressure is no more than 10 -3 Pa;
[0073] S3, vacuum brazing heat treatment: the vacuum brazing furnace is heated up, and the GH2909 alloy parts with cleaned surfaces in S1 are subjected to vacuum brazing heat treatment, the temperature of vacuum brazing heat treatment is 1010°C, and the temperature is kept for 25 minutes; the temperature is raised to 560°C at a rate of 15°C / min and kept for 10 minutes, and then the temperature is raised to 920°C at a rate of 20°C / min and kept for 10 minutes, and finally the temperature is raised to 1010°C at a rate of 7°C / min; after brazing, the parts are cooled with the furnace at a cooling rate of 4°C / min, cooled to 80°C, taken out and air-cooled to room temperature at a cooling rate of 70°C / min, and the GH2909 alloy parts after vacuum brazing treatment are obtained;
[0074] S4. Two aging treatments: The GH2909 alloy parts after S3 vacuum brazing heat treatment were subjected to two aging treatments. The temperature was raised to 745°C at a rate of 20°C / min and kept at this temperature for 4 hours. Then, the parts were cooled to 620°C at a rate of 55°C / h and kept at this temperature for 4 hours. Then, the parts were taken out and air-cooled to room temperature at a rate of 50-80°C / min to obtain GH2909 alloy parts.
[0075] The shape of the GH2909 alloy component of this comparative example is a bar with a size of Φ150mm and a sampling size of Φ8mm; the tensile strength at room temperature is 1180-1240MPa, with a standard deviation of 15-27MPa; the yield strength at room temperature is 920-955MPa, with a standard deviation of 7-15MPa; the elongation at room temperature is 14.7-19.8%, with a standard deviation of 0.7-1.2%; the cross-sectional shrinkage at room temperature is 24-37%, with a standard deviation of 2.9-5.6%; The temperature hardness is 357-365HB, and the standard deviation is 5-8HB; the tensile strength at 650℃ is 880-950MPa, and the standard deviation is 17-33MPa; the yield strength at 650℃ is 745-800MPa, and the standard deviation is 26-40MPa; the elongation at 650℃ is 14.5-21.8%, and the standard deviation is 2.4-7.7%; the cross-sectional shrinkage at 650℃ is 27.0-42.5%, and the standard deviation is 4.7-9.2%.
[0076] The microstructure of the GH2909 alloy parts prepared in this comparative example after vacuum brazing + two aging processes consists of a γ solid solution with a volume fraction of 74.93%, a γ′ phase with a volume fraction of 18.11%, a Laves phase with a volume fraction of 4.78%, and an ε phase with a volume fraction of 2.18% (the γ solid solution is generally not studied, and its shape and size are not fixed); among them, the γ′ phase is cubic in shape, with an average size of 32.77 nm; the Laves phase is spherical or short rod-shaped, with an average major axis length of 1.72 μm and an average minor axis length of 0.81 μm; the ε phase is needle-shaped, with an average length of 1.69 μm.
[0077] Comparative Example 3
[0078] A vacuum brazing and heat treatment process for GH2909 alloy parts, wherein the elements are as follows by mass percentage: C 0.01%, Si 0.40%, Co 13.48%, Ni 38.06%, Ti 1.64, Nb 4.88%, Al 0.031%, Mo 0.04%, and the balance is Fe and unavoidable impurities; the vacuum brazing and heat treatment process for GH2909 alloy parts comprises the following steps:
[0079] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the GH2909 alloy component is in the shape of a rod, with a size of Φ150 mm, a sampling size of Φ8 mm, and a state before brazing of standard short-time double aging 2. The mechanical properties are shown in Table 5 below:
[0080] Table 5
[0081] Test temperature / ℃ Tensile strength / MPa Standard deviation / MPa Room temperature 1211、1192、1242、1228、1250、1219 19.3 650 900、865、885、935、895、921 22.8 Test temperature / ℃ Yield strength / MPa Standard deviation / MPa Room temperature 960、931、953、942、935、945 9.9 650 750、725、734、804、779、781 28.0 Test temperature / ℃ Elongation / % Standard Deviation / % Room temperature 13.5、15.4、17.1、14.4、15.4、14.1 1.2 650 11.5、12.7、17.5、21.2、24、16 4.4 Test temperature / ℃ Shrinkage after breaking / % Standard Deviation / % Room temperature 26、33、37、28、31、22 4.8 650 24、37、31、38、38、27 5.5 Test temperature / ℃ Hardness / HB Standard deviation / HB Room temperature 361.1、373.3、368.5、359.1、360.1、367.5 5.2 ;
[0082] S2. Vacuuming: Place the GH2909 alloy parts with cleaned surface in S1 into a vacuum brazing furnace and evacuate until the pressure is no more than 10 -3 Pa;
[0083] S3, vacuum brazing heat treatment: the vacuum brazing furnace is heated up, and the GH2909 alloy parts with cleaned surfaces in S1 are subjected to vacuum brazing heat treatment, the temperature of vacuum brazing heat treatment is 1000°C, and the temperature is kept for 25 minutes; the temperature is raised to 560°C at a rate of 15°C / min and kept for 10 minutes, and then the temperature is raised to 920°C at a rate of 20°C / min and kept for 10 minutes, and finally the temperature is raised to 1000°C at a rate of 7°C / min; after brazing is completed, the parts are cooled with the furnace at a cooling rate of 3°C / min, cooled to 80°C, taken out and air-cooled to room temperature at a cooling rate of 70°C / min, and the GH2909 alloy parts after vacuum brazing are obtained;
[0084] S4. Two aging treatments: The GH2909 alloy parts after S3 vacuum brazing heat treatment were subjected to two aging treatments. The temperature was raised to 745°C at a rate of 20°C / min and kept at this temperature for 4 hours. The parts were then taken out for water cooling at a rate of 50°C / s. The temperature was then raised to 620°C at a rate of 20°C / min and kept at this temperature for 4 hours. The parts were then taken out for air cooling at a rate of 70°C / min. GH2909 alloy parts with improved room temperature strength and stability were obtained.
[0085] The shape of the GH2909 alloy component of this comparative example is a bar with a size of Φ150mm and a sampling size of Φ8mm; the tensile strength at room temperature is 1170-1220MPa, with a standard deviation of 13-26MPa; the yield strength at room temperature is 910-945MPa, with a standard deviation of 5-13MPa; the elongation at room temperature is 16.7-20.8%, with a standard deviation of 0.9-1.7%; the cross-sectional shrinkage at room temperature is 25-38%, with a standard deviation of 1.8-5.4%; The temperature hardness is 360-369HB, and the standard deviation is 5-9HB; the tensile strength at 650℃ is 880-945MPa, and the standard deviation is 17-40MPa; the yield strength at 650℃ is 750-800MPa, and the standard deviation is 26-37MPa; the elongation at 650℃ is 13.7-20.8%, and the standard deviation is 2.7-5.9%; the cross-sectional shrinkage at 650℃ is 26.7-44.2%, and the standard deviation is 2.9-8.2%.
[0086] The microstructure of the GH2909 alloy component of this comparative example after vacuum brazing + two aging processes consists of 70.55% volume fraction of γ solid solution, 22.44% volume fraction of γ′ phase, 4.76% volume fraction of Laves phase and 2.25% ε phase (γ solid solution is generally not studied, and its shape and size are not fixed); among them, the shape of γ′ phase is cubic, and the average size is 33.57nm; the shape of Laves phase is spherical or short rod, with an average major axis length of 1.69μm and an average minor axis length of 0.76μm; the shape of ε phase is needle-shaped, and the average length is 1.89μm.
[0087] Comparing Example 1 with Comparative Example 1, Example 1 optimizes the cooling method after vacuum brazing and the subsequent heat treatment method in Comparative Example 1, adopts slower furnace cooling instead of Ar gas fast cooling, and adopts low-temperature one-time aging instead of the traditional double aging process; Comparing Example 1 with Comparative Example 2, Example 1 optimizes the heat treatment method after brazing in Comparative Example 2, and adopts low-temperature one-time aging instead of the traditional double aging heat treatment; Comparing Example 1 with Comparative Example 3, Example 1 optimizes the heat treatment method after brazing in Comparative Example 3, and adopts low-temperature one-time aging instead of the staged double aging heat treatment.
[0088] Compared with comparative examples 1-3, Example 1 optimizes the process steps and precipitates extremely dense and fine γ′ phase in the alloy matrix. From the data, we can find that the size of the γ′ phase in Example 1 is much smaller than that in comparative examples 1-3, and the plasticity is equivalent while the strength is improved.
[0089] Under the premise of being in line with actual production, the present invention proposes a vacuum brazing and heat treatment process suitable for GH2909 alloy. Compared with multiple brazing processes, it reduces the coarsening of Laves phase and the grain growth of alloy parts caused by the dissolution of Laves phase. Due to the limitation of vacuum conditions, the alloy parts cannot be taken out and air-cooled immediately. The present invention uses this section to allow the alloy to be furnace-cooled, appropriately reduce the cooling rate, regulate the precipitation of a small amount of γ′ phase, and then cooperate with a one-step aging process. This process simplifies the traditional standard aging process. It solves the problem that the tensile strength and yield strength of forgings sometimes do not meet the standards or the excess of the standards is very small and unstable.
[0090] Compared with the traditional standard heat treatment process, the heat treatment of the present invention adopts a one-step aging process, which replaces the relatively complex two-step aging process under the same aging time. The alloy γ′ phase precipitates densely in the cooling stage after solutionization, and precipitates supplementarily during the one-step aging heat treatment process, and no excessive growth and phase transformation occur during the process. After this heat treatment, the uniformity of the γ′ phase distribution inside the grains is improved, which has an unexpected effect on improving the strength and stability of alloy components. Multiple sets of mechanical property test results show that compared with traditional brazing and aging processes, after treatment with the method described in the present invention, the room temperature tensile strength and yield strength of the alloy are increased by 120MPa and 90MPa respectively, and the standard deviation of the room temperature yield strength is reduced by more than 30%.
[0091] Example 2
[0092] A vacuum brazing and heat treatment process for GH2909 alloy parts, wherein the GH2909 alloy used is in a rod shape with a size of Φ200 mm, and the composition of each element by mass percentage is: C 0.022%, Si 0.26%, Co 14.08%, Ni 37.66%, Ti 1.67%, Nb 5.09%, Al 0.12%, Mo 0.50%, and the balance is Fe and unavoidable impurities; the vacuum brazing and heat treatment process for GH2909 alloy parts comprises the following steps:
[0093] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the shape of the GH2909 alloy component is a rod, the size is Φ200mm, the sampling size is Φ8mm, the state before brazing is standard short-time double aging 2, and the mechanical properties are shown in Table 6 below:
[0094] Table 6
[0095] Test temperature / ℃ Tensile strength / MPa Standard deviation / MPa Room temperature 1211、1197、1232、1250、1228、1219 16.7 650 901、868、897、934、893、927 21.9 Test temperature / ℃ Yield strength / MPa Standard deviation / MPa Room temperature 959、942、954、939、937、948 7.9 650 751、734、774、805、769、800 24.8 Test temperature / ℃ Elongation / % Standard Deviation / % Room temperature 13.7、15.4、18.1、14.4、15.2、14.3 1.4 650 11.7、12.7、16.5、21.2、22.8、15.2 4.1 Test temperature / ℃ Shrinkage after breaking / % Standard Deviation / % Room temperature 25、33、37、28、31、27 4.0 650 28、37、31、38、38、29 4.2 Test temperature / ℃ Hardness / HB Standard deviation / HB Room temperature 361.1、373.3、368.5、359.1、360.1、367.5 5.2 ;
[0096] S2. Vacuuming: Place the GH2909 alloy parts with cleaned surface in S1 into a vacuum brazing furnace and evacuate until the pressure is no more than 10 -3 Pa;
[0097] S3, vacuum brazing heat treatment: the vacuum brazing furnace is heated up, and the GH2909 alloy parts with cleaned surfaces in S1 are subjected to vacuum brazing heat treatment, the temperature of vacuum brazing heat treatment is 1000°C, and the temperature is kept for 25 minutes; the temperature is raised to 550°C at a rate of 15°C / min and kept for 10 minutes, and then the temperature is raised to 940°C at a rate of 20°C / min, and kept for 10 minutes, and finally the temperature is raised to 1000°C at a rate of 7°C / min; after brazing is completed, the parts are cooled with the furnace at a cooling rate of 3°C / min, cooled to 80°C, taken out and air-cooled to room temperature at a cooling rate of 70°C / min, and the GH2909 alloy parts after vacuum brazing are obtained;
[0098] S4. Primary aging treatment: The GH2909 alloy parts after S3 vacuum brazing heat treatment were subjected to primary aging treatment at a temperature of 630°C for 7.5 hours at a heating rate of 10°C / min and an air cooling rate of 70°C / min. Finally, GH2909 alloy parts with improved room temperature strength and stability were obtained.
[0099] The GH2909 alloy component of this embodiment is in the shape of a rod, with a size of Φ200 mm and a sampling size of Φ8 mm. After vacuum brazing and one-time aging, the mechanical properties are shown in Table 7 below:
[0100] Table 7
[0101] Test temperature / ℃ Tensile strength / MPa Standard deviation / MPa Room temperature 1382、1379、1384、1369、1389、1374 6.5 650 1015、1011、1008、998、1014、1021 7.1 Test temperature / ℃ Yield strength / MPa Standard deviation / MPa Room temperature 1024、1031、1035、1028、1039、1027 5.1 650 840、824、827、834、822、831 6.1 Test temperature / ℃ Elongation / % Standard Deviation / % Room temperature 19.1、20.1、20.4、21.5、19.9、19.7 0.7 650 18.4、17.6、20.8、23.1、18.9、13.5 2.9 Test temperature / ℃ Shrinkage after breaking / % Standard Deviation / % Room temperature 35、34、33、33、37、36 1.5 650 36、38、42、37、40、39 2.0 Test temperature / ℃ Hardness / HB Standard deviation / HB Room temperature 381.3、373.3、377.8、376.2、382.6、378.8 2.9 ;
[0102] The microstructure of the GH2909 alloy component of this embodiment after vacuum brazing + primary aging consists of a γ solid solution with a volume fraction of 82.00%, a γ′ phase with a volume fraction of 11.99%, a Laves phase with a volume fraction of 4.32%, and an ε phase with a volume fraction of 1.69% (the γ solid solution is generally not studied, and its shape and size are not fixed); among them, the γ′ phase is in the shape of a small sphere or a cube, with an average size of 17.69nm; the Laves phase is in the shape of a sphere or a short rod, with an average major axis length of 1.52μm and an average minor axis length of 0.70μm; the ε phase is in the shape of a needle, with an average length of 1.51μm.
[0103] Example 3
[0104] A vacuum brazing and heat treatment process for GH2909 alloy parts, wherein the GH2909 alloy used is in a rod shape with a size of Φ220 mm, and the composition of each element is recorded by mass percentage as follows: C 0.01%, Si 0.38%, Co 13.42%, Ni 37.64%, Ti 1.55%, Nb 4.68%, Al 0.039%, Mo 0.03%, and the balance is Fe and unavoidable impurities; the vacuum brazing and heat treatment process for GH2909 alloy parts comprises the following steps:
[0105] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the GH2909 alloy component is in the shape of a rod, with a size of Φ220 mm, a sampling size of Φ8 mm, and a state before brazing of standard short-time double aging 2. The mechanical properties are shown in Table 8 below:
[0106] Table 8
[0107]
[0108]
[0109] S2. Vacuuming: Place the GH2909 alloy parts with cleaned surface in S1 into a vacuum brazing furnace and evacuate until the pressure is no more than 10 -3 Pa;
[0110] S3, vacuum brazing heat treatment: the vacuum brazing furnace is heated up, and the GH2909 alloy parts with cleaned surfaces in S1 are subjected to vacuum brazing heat treatment, the temperature of vacuum brazing heat treatment is 1020°C, and the temperature is kept for 15 minutes; the temperature is raised to 580°C at a rate of 15°C / min and kept for 10 minutes, and then the temperature is raised to 930°C at a rate of 20°C / min, and kept for 10 minutes, and finally the temperature is raised to 1020°C at a rate of 10°C / min; after brazing is completed, the parts are cooled with the furnace at a cooling rate of 3°C / min, cooled to 80°C, taken out and air-cooled to room temperature at a cooling rate of 70°C / min, and the GH2909 alloy parts after vacuum brazing are obtained;
[0111] S4. Primary aging treatment: The GH2909 alloy parts after S3 vacuum brazing heat treatment were subjected to primary aging treatment at a temperature of 620°C for 8 hours at a heating rate of 15°C / min and an air cooling rate of 70°C / min. After air cooling, GH2909 alloy parts with improved room temperature strength and stability were obtained.
[0112] The GH2909 alloy component of this embodiment is in the shape of a rod, with a size of Φ220 mm and a sampling size of Φ8 mm. After vacuum brazing and one-time aging, the mechanical properties are shown in Table 9 below:
[0113] Table 9
[0114]
[0115]
[0116] The microstructure of the GH2909 alloy component of this embodiment after vacuum brazing + primary aging consists of 80.07% volume fraction of γ solid solution, 13.79% volume fraction of γ′ phase, 4.44% volume fraction of Laves phase and 1.70% ε phase (γ solid solution is generally not studied, and its shape and size are not fixed); among them, the shape of γ′ phase is small spherical or cubic, with an average size of 18.54nm; the shape of Laves phase is spherical or short rod, with an average major axis length of 1.60μm and an average minor axis length of 0.75μm; the shape of ε phase is needle-shaped, with an average length of 1.31μm.
[0117] Example 4
[0118] A vacuum brazing and heat treatment process for GH2909 alloy parts, wherein the GH2909 alloy used is a ring with an outer diameter of 600 mm, an inner diameter of 500 mm, and a height of 70 mm, and the composition of each element by mass percentage is: C 0.01%, Si 0.39%, Co 13.49%, Ni 38.05%, Ti 1.62%, Nb 4.78%, Al 0.031%, Mo 0.04%, and the balance is Fe and unavoidable impurities; the vacuum brazing and heat treatment process for GH2909 alloy parts comprises the following steps:
[0119] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the GH2909 alloy component is in the shape of a ring, with an outer diameter of 600 mm, an inner diameter of 500 mm, a height of 70 mm, and a chordal sampling with a sampling size of Φ8 mm. The state before brazing is standard short-time double aging 2, and the mechanical properties are shown in Table 10 below:
[0120] Table 10
[0121] Test temperature / ℃ Tensile strength / MPa Standard deviation / MPa Room temperature 1225、1232、1238、1228、1214、1230 7.3 650 999、998、1008、1010、1002、1000 6.8 Test temperature / ℃ Yield strength / MPa Standard deviation / MPa Room temperature 945、968、958、967、950、983 7.9 650 813、775、800、810、795、789 12.8 Test temperature / ℃ Elongation / % Standard Deviation / % Room temperature 14.2、15.5、14.5、14.8、14.8、11.9 1.1 650 17.5、18.2、19.2、18.8、20.1、24 2.1 Test temperature / ℃ Shrinkage after breaking / % Standard Deviation / % Room temperature 29、30、31、34、37、36 3.0 650 32、35、36、34、37、35 1.6 Test temperature / ℃ Hardness / HB Standard deviation / HB Room temperature 368.1、370.1、373.4、368.7、362.5、368.3 3.2 ;
[0122] S2. Vacuuming: Place the GH2909 alloy parts with cleaned surface in S1 into a vacuum brazing furnace and evacuate until the pressure is no more than 10 -3 Pa;
[0123] S3, vacuum brazing heat treatment: the vacuum brazing furnace is heated up, and the GH2909 alloy parts with cleaned surfaces in S1 are subjected to vacuum brazing heat treatment, the temperature of vacuum brazing heat treatment is 1040°C, and the temperature is kept for 10 minutes; the temperature is raised to 550°C at a rate of 15°C / min and kept for 10 minutes, and then the temperature is raised to 940°C at a rate of 20°C / min, and kept for 10 minutes, and finally the temperature is raised to 1040°C at a rate of 10°C / min; after brazing is completed, the parts are cooled with the furnace at a cooling rate of 3°C / min, cooled to 80°C, taken out and air-cooled to room temperature at a cooling rate of 70°C / min, and the GH2909 alloy parts after vacuum brazing are obtained;
[0124] S4. Primary aging treatment: The GH2909 alloy parts after S3 vacuum brazing heat treatment were subjected to primary aging treatment at a temperature of 620°C for 8.5 hours at a heating rate of 15°C / min and an air cooling rate of 70°C / min. After air cooling, GH2909 alloy parts with improved room temperature strength and stability were obtained.
[0125] The GH2909 alloy component of this embodiment is annular in shape, with an outer diameter of 600 mm, an inner diameter of 500 mm, and a height of 70 mm. The chordal sampling has a sampling size of Φ8. After vacuum brazing and primary aging, the mechanical properties are shown in Table 11 below:
[0126] Table 11
[0127] Test temperature / ℃ Tensile strength / MPa Standard deviation / MPa Room temperature 1372、1378、1383、1388、1375、1380 5.8 650 1005、1015、1020、1008、1002、1016 6.9 Test temperature / ℃ Yield strength / MPa Standard deviation / MPa Room temperature 1038、1035、1037、1042、1036、1040 2.5 650 825、822、828、824、826、821 2.6 Test temperature / ℃ Elongation / % Standard Deviation / % Room temperature 18.5、19.8、19.2、20.4、19.1、18.9 0.7 650 18.8、19.2、21.5、22.8、18.2、16.2 2.3 Test temperature / ℃ Shrinkage after breaking / % Standard Deviation / % Room temperature 35、33、32、33、35、34 1.2 650 36、39、41、35、38、37 2.1 Test temperature / ℃ Hardness / HB Standard deviation / HB Room temperature 379.2、381.8、376.4、377.5、380.9、378.5 2.0 ;
[0128] The microstructure of the GH2909 alloy component of this embodiment after vacuum brazing + primary aging consists of 80.05% volume fraction of γ solid solution, 13.50% volume fraction of γ′ phase, 4.48% volume fraction of Laves phase and 1.97% ε phase (γ solid solution is generally not studied, and its shape and size are not fixed); among them, the shape of γ′ phase is small spherical or cubic, with an average size of 18.72nm; the shape of Laves phase is spherical or short rod, with an average major axis length of 1.78μm and an average minor axis length of 0.81μm; the shape of ε phase is needle-shaped, with an average length of 1.52μm.
[0129] Example 5
[0130] A vacuum brazing and heat treatment process for GH2909 alloy parts, wherein the GH2909 alloy used is a ring with an outer diameter of 400 mm, an inner diameter of 300 mm, and a height of 50 mm, and the composition of each element by mass percentage is: C 0.01%, Si 0.40%, Co 13.48%, Ni 38.06%, Ti 1.64%, Nb 4.88%, Al 0.031%, Mo 0.04%, and the balance is Fe and unavoidable impurities; the vacuum brazing and heat treatment process for GH2909 alloy parts comprises the following steps:
[0131] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the shape of the GH2909 alloy component is annular, with an outer diameter of 400 mm, an inner diameter of 300 mm, a height of 50 mm, and a chordal sampling with a sampling size of Φ8 mm. The state before brazing is standard short-time double aging 2, and the mechanical properties are shown in Table 12 below:
[0132] Table 12
[0133]
[0134]
[0135] S2. Vacuuming: Place the GH2909 alloy parts with cleaned surface in S1 into a vacuum brazing furnace and evacuate until the pressure is no more than 10 -3 Pa;
[0136] S3, vacuum brazing heat treatment: the vacuum brazing furnace is heated up, and the GH2909 alloy component with the cleaned surface of S1 is subjected to vacuum brazing heat treatment, the temperature of the vacuum brazing heat treatment is 1000°C, and the temperature is kept for 30 minutes; the temperature is raised to 620°C at a rate of 15°C / min and kept for 10 minutes, and then the temperature is raised to 910°C at a rate of 20°C / min, and kept for 10 minutes, and finally the temperature is raised to 1000°C at a rate of 10°C / min; after the brazing is completed, the furnace is cooled at a cooling rate of 3°C / min, and the component is cooled to 80°C and taken out and air-cooled to room temperature at a cooling rate of 70°C / min, thereby obtaining the GH2909 alloy component after vacuum brazing heat treatment;
[0137] S4. Primary aging treatment: The GH2909 alloy parts after S3 vacuum brazing heat treatment were subjected to primary aging treatment at a temperature of 625°C for 8.5 hours at a heating rate of 20°C / min and an air cooling rate of 70°C / min. After air cooling, GH2909 alloy parts with improved room temperature strength and stability were obtained.
[0138] The GH2909 alloy component of this embodiment is annular in shape, with an outer diameter of 400 mm, an inner diameter of 300 mm, and a height of 50 mm. The chordal sampling has a sampling size of Φ8. After vacuum brazing and primary aging, the mechanical properties are shown in Table 13 below:
[0139] Table 13
[0140]
[0141]
[0142] The microstructure of the GH2909 alloy component of this embodiment after vacuum brazing + primary aging consists of a γ solid solution with a volume fraction of 79.13%, a γ′ phase with a volume fraction of 14.75%, a Laves phase with a volume fraction of 4.76%, and an ε phase with a volume fraction of 1.36% (the γ solid solution is generally not studied, and its shape and size are not fixed); among them, the γ′ phase is in the shape of a small sphere or a cube, with an average size of 18.88 nm; the Laves phase is in the shape of a sphere or a short rod, with an average major axis length of 1.67 μm and an average minor axis length of 0.93 μm; the ε phase is in the shape of a needle, with an average length of 1.71 μm.
[0143] It should be understood that the term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship, but it may also indicate an "and / or" relationship. Please refer to the context for specific understanding.
[0144] In the present invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, at least one of a, b, or c can be represented by: a, b, c, ab, ac, bc, or abc, where a, b, c can be single or multiple.
[0145] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0146] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A vacuum brazing and heat treatment process for GH2909 alloy parts, characterized in that: The vacuum brazing and heat treatment process of the GH2909 alloy parts is as follows: S1. Surface pretreatment: pretreating the surface of the GH2909 alloy component to obtain a GH2909 alloy component with a clean surface; S2, vacuuming: Place the GH2909 alloy parts with cleaned surfaces in S1 in a vacuum brazing furnace and vacuumize; S3, vacuum brazing heat treatment: the vacuum brazing furnace is heated up, and the GH2909 alloy parts with cleaned surfaces in S1 are subjected to vacuum brazing heat treatment, and then cooled with the furnace, and then air-cooled after furnace cooling, to obtain the GH2909 alloy parts after vacuum brazing heat treatment; S4. Primary aging treatment: Perform primary aging treatment on the GH2909 alloy parts after S2 vacuum brazing heat treatment, and obtain GH2909 alloy parts with improved room temperature strength and stability after air cooling.
2. The vacuum brazing and heat treatment process of GH2909 alloy parts according to claim 1 is characterized in that: The shape of the GH2909 alloy parts in S1 is a bar with a size of Φ150mm, Φ200mm or Φ220mm. The treatment state is standard double aging heat treatment 2 (845℃×(4±0.5)h / FC→620℃×(4±0.5)h / AC); the tensile strength at room temperature is 1190-1250MPa, with a standard deviation of 18-29MPa; the yield strength at room temperature is 930-960MPa, with a standard deviation of 9-17MPa; the elongation at room temperature is 13.7-17.8%, with a standard deviation of 0.9-1.5%; the cross section at room temperature is The shrinkage rate is 22-33%, and the standard deviation is 3.9-5.8%; the room temperature hardness is 350-365HB, and the standard deviation is 5-11HB; the tensile strength at 650℃ is 860-970MPa, and the standard deviation is 19-31MPa; the yield strength at 650℃ is 715-800MPa, and the standard deviation is 25-43MPa; the elongation at 650℃ is 12.5-20.4%, and the standard deviation is 2.3-6.7%; the cross-sectional shrinkage rate at 650℃ is 26.0-40.5%, and the standard deviation is 4.5-8.9%.
3. The vacuum brazing and heat treatment process of GH2909 alloy parts according to claim 1, characterized in that: The shape of the GH2909 alloy parts in S1 is annular, with dimensions of 400-600mm in outer diameter, 300-500mm in inner diameter, and 70-90mm in height. The samples are taken in the chord direction, and the treatment state is standard double aging heat treatment 2 (845℃×(4±0.5)h / FC→620℃×(4±0.5)h / AC); the tensile strength at room temperature is 1200-1240MPa, with a standard deviation of 15-27MPa; the yield strength at room temperature is 910-970MPa, with a standard deviation of 20-45MPa; the elongation at room temperature is 14.0-18.8%, with a standard deviation of 1.2-2 .3%; the section shrinkage at room temperature is 24-37%, with a standard deviation of 3.6-5.9%; the room temperature hardness is 350-365HB, with a standard deviation of 6-11HB; the tensile strength at 650℃ is 930-970MPa, with a standard deviation of 20-31MPa; the yield strength at 650℃ is 770-810MPa, with a standard deviation of 25-43MPa; the elongation at 650℃ is 12.5-29.4%, with a standard deviation of 3.8-9.7%; the section shrinkage at 650℃ is 26.0-44.5%, with a standard deviation of 6.7-10.9%.
4. The vacuum brazing and heat treatment process of GH2909 alloy parts according to claim 1, characterized in that: The shape of the GH2909 alloy component in S1 is a square billet with a size of 90mm×90mm×90mm. The treatment state is standard double aging heat treatment 2 (845℃×(4±0.5)h / FC→620℃×(4±0.5)h / AC); the tensile strength at room temperature is 1200-1230MPa, with a standard deviation of 15-28MPa; the yield strength at room temperature is 890-945MPa, with a standard deviation of 19-35MPa; the elongation at room temperature is 14.7-18.2%, with a standard deviation of 0.7-2.1%; the cross-sectional shrinkage at room temperature is The rate is 26-37%, and the standard deviation is 2.7-5.9%; the room temperature hardness is 360-365HB, and the standard deviation is 2-7HB; the tensile strength at 650℃ is 935-980MPa, and the standard deviation is 15-25MPa; the yield strength at 650℃ is 784-820MPa, and the standard deviation is 20-40MPa; the elongation at 650℃ is 15.5-29.4%, and the standard deviation is 3.8-9.3%; the cross-sectional shrinkage at 650℃ is 27.0-47.5%, and the standard deviation is 6.7-11.9%.
5. The vacuum brazing and heat treatment process of GH2909 alloy parts according to claim 1, characterized in that: The pretreatment in S1 includes removing the surface oxide layer or oil stains, and finally cleaning and drying to obtain a GH2909 alloy component with a clean surface; the vacuuming in S2 is to vacuumize to a pressure not greater than 10 -3 Pa.
6. The vacuum brazing and heat treatment process of GH2909 alloy parts according to claim 1, characterized in that: The temperature of vacuum brazing heat treatment in S3 is 1000-1040℃, and the temperature is kept for 10-30min; it needs to be heated to 550-650℃ at a rate of 10-15℃ / min and kept for 10-20min, then heated to 880-940℃ at a rate of 15-20℃ / min and kept for 15-30min, and finally heated to the brazing insulation temperature of 1000-1040℃ at a rate of 5-10℃ / min; then cooled with the furnace at a cooling rate of 3-8℃ / min, cooled with the furnace to below 80℃ and directly taken out of the furnace, and the air cooling rate is 50-80℃ / min, and the insulation time after reaching the brazing temperature of 1000-1040℃ in this stage is 10-30min.
7. The vacuum brazing and heat treatment process of GH2909 alloy parts according to claim 1, characterized in that: The temperature of the primary aging treatment in S4 is 620±10°C, and the temperature is kept for 8±0.5h, and the heating rate is 10-30°C / min; the mixture is taken out and air-cooled to room temperature, and the air-cooling rate is 50-80°C / min.
8. The vacuum brazing and heat treatment process of GH2909 alloy parts according to claim 2, characterized in that: S3 is a bar with a size of Φ150mm, Φ200mm or Φ220mm. The treatment state is vacuum brazing + primary aging ((1000-1040)℃×(15-30)min / FC+620℃×(8±0.5)h / AC); the tensile strength at room temperature is 1350-1380MPa, with a standard deviation of 10-17MPa; the yield strength at room temperature is 1020-1050MPa, with a standard deviation of 9-14MPa; the elongation at room temperature is 17.9-23.2%, with a standard deviation of 0.8-1.7%; the cross section at room temperature is The shrinkage rate is 27-39%, and the standard deviation is 2.9-4.8%; the room temperature hardness is 370-385HB, and the standard deviation is 3-8HB; the tensile strength at 650℃ is 1005-1025MPa, and the standard deviation is 12-26MPa; the yield strength at 650℃ is 820-870MPa, and the standard deviation is 25-33MPa; the elongation at 650℃ is 11.5-21.4%, and the standard deviation is 2.3-5.7%; the cross-sectional shrinkage rate at 650℃ is 35.0-40.5%, and the standard deviation is 2.7-4.9%.
9. The vacuum brazing and heat treatment process of GH2909 alloy parts according to claim 3, characterized in that: The shape of S3 is annular, with dimensions of 400-600mm in outer diameter, 300-500mm in inner diameter, and 70-90mm in height. The samples are taken in the chord direction, and the treatment state is vacuum brazing + primary aging ((1000-1040)℃×(15-30)min / FC+620℃×(8±0.5)h / AC); the tensile strength at room temperature is 1340-1370MPa, with a standard deviation of 11-15MPa; the yield strength at room temperature is 1025-1060MPa, with a standard deviation of 10-14MPa; the elongation at room temperature is 18.8-24.5%, with a standard deviation of 0.7- 1.4%; the section shrinkage at room temperature is 30-39%, with a standard deviation of 2.7-4.2%; the room temperature hardness is 370-385HB, with a standard deviation of 3-9HB; the tensile strength at 650℃ is 1000-1020MPa, with a standard deviation of 12-20MPa; the yield strength at 650℃ is 830-870MPa, with a standard deviation of 20-30MPa; the elongation at 650℃ is 11.5-20.4%, with a standard deviation of 3.7-5.1%; the section shrinkage at 650℃ is 35.0-41.5%, with a standard deviation of 2.7-3.8%.
10. The vacuum brazing and heat treatment process of GH2909 alloy parts according to claim 4, characterized in that: The shape of S3 is square billet, the size is 90mm×90mm×90mm, and the treatment state is standard double aging heat treatment 2 (845℃×(4±0.5)h / FC→620℃×(4±0.5)h / AC); the tensile strength at room temperature is 1200-1230MPa, and the standard deviation is 15-28MPa; the yield strength at room temperature is 890-945MPa, and the standard deviation is 19-35MPa; the elongation at room temperature is 14.7-18.2%, and the standard deviation is 0.7-2.1%; the cross-sectional shrinkage at room temperature is 26-3 7%, standard deviation is 2.7-5.9%; room temperature hardness is 360-365HB, standard deviation is 2-7HB; tensile strength at 650℃ is 935-980MPa, standard deviation is 15-25MPa; yield strength at 650℃ is 784-820MPa, standard deviation is 20-40MPa; elongation at 650℃ is 15.5-29.4%, standard deviation is 3.8-9.3%; section shrinkage at 650℃ is 27.0-47.5%, standard deviation is 6.7-11.9%.
Citation Information
Patent Citations
High-temperature alloy mechanical heat treatment method
CN110699531A
Process for improving high-temperature yield strength of GH4738 alloy forging subjected to vacuum brazing
CN113637928A
High-performance brazing method for third-generation single crystal high-temperature alloy
CN113909610A
Brazing method for improving high-temperature welding performance of nickel-based alloy joint and prepared multi-layer welding joint
CN119035686A
Manufacture of aluminum alloy soft sheet for vacuum brazing
JP1990259052A